2022
DOI: 10.15244/pjoes/147592
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ANN, GEP, and Regression Models to Estimate the Discharge Coefficient for the Rectangular Broad-Crested Weir

Abstract: Weirs are important hydraulic structures that have been used extensively to measure and control water flow in irrigation and drainage networks, reservoirs, sewage disposal systems, flood control, and river. These structures, such as valves, are vital components in water management in irrigation canals [1][2][3]. Weirs are different types, and they are provided with particular forms for various applications. Weir of multiple classes is offered specific conditions for numerous applications. The essential spillwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…Emami et al 26 used the Walnut algorithm and SVR method to predict the C d of triangular labyrinth weirs. Safari et al 27 evaluated ANN, GEP, and regression models to estimate the C d of the broad-crested weir. The results showed that ANN estimates the C d better than GEP models and regression models.…”
Section: Introductionmentioning
confidence: 99%
“…Emami et al 26 used the Walnut algorithm and SVR method to predict the C d of triangular labyrinth weirs. Safari et al 27 evaluated ANN, GEP, and regression models to estimate the C d of the broad-crested weir. The results showed that ANN estimates the C d better than GEP models and regression models.…”
Section: Introductionmentioning
confidence: 99%
“…Scientists have examined the utilization of artificial intelligence methods, such as artificial neural networks, adaptive neuro fuzzy inference systems, support vector machines, and group technique of data processing [26,37,42]. Safari et al [43] evaluated various models -Artificial Neural Networks (ANN), Gene Expression Programming (GEP), and regression models -in estimating the discharge coefficient for rectangular broadcrested weirs. The main finding seems to be a comparative analysis of these models in accurately predicting the flow over a specific type of weir, highlighting the strengths and weaknesses of each approach.…”
Section: Introductionmentioning
confidence: 99%